KEUANGAN KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH MAWAR JATIM - Have Zulkarnaen; Fatichatur Rachmaniyah (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2022)
ABSTRACT This type of research is quantitative descriptive research. The analysis method used is financial ratio analysis. The results of the study show that: (1) the cash ratio in 2018-2020 is included in the bad criteria because it is still below the predetermined standard, the cash ratio value is 26.06%, 34.73%, 66.56%. (2) the DtAR in 2018-2020 has increased, namely 85.29%, 77.81%, 76.83% with unfavorable criteria. (3) the DtER in 2018-2020 there is quite an increase in the ratio, but it is still in bad criteria. (4) ROA in 2018-2020 fluctuated, namely 2.26%, 5.24%, 3.16% with fairly good criteria. (5) ROE in 2018-2020 fluctuated, namely 18.23%, 30.96%, 13.64% with good criteria. (6) the NPM in 2018-2020 fluctuated, namely 33.75%, 62.06%, 58.47% with very good criteria. The Mawar Jatim needs to increase its cash and should reduce the amount of its debt. ,